Transcriptome Co-expression Network Analysis Identifies Key Genes Regulating Conchosporangia Maturation of Pyropia haitanensis - Lin, Yinghui; Xu, Kai; Xu, Yan; Ji, Dehua; Chen, Changsheng; Wang, Wenlei; Xie, Chaotian (Frontiers in Genetics, 2021)
Conchosporangia maturation is crucial for the yield of Pyropia/Porphyra. However, the molecular mechanisms underlying this process are poorly understood. In this study, we selected two strains of Pyropia haitanensis that show significant differences in conchosporangia maturation as materials to produce RNA-Seq libraries. Then, we identified key molecular pathways and genes involved in conchosporangia maturation by conducting a weighted gene co-expression network analysis (WGCNA). Two specific modules were identified, and included functions such as phosphorus metabolism, lipid metabolism, and the phosphatidylinositol signaling system. The hub genes that responded positively during conchosporangia maturation encoded diacylglycerol kinase (DGK) and phosphatidylinositol-3-phosphate-5-kinase (PIKFYVE), which are involved in the synthesis of phosphatidic acid (PA), a key component of lipid metabolism. A full-length DGK sequence of P. haitanensis, designated as PhDGK1, was obtained by rapid-amplification of cDNA ends. Conserved motif and phylogenetic tree analyses showed that PhDGK1 belongs to DGK Cluster II. The transcript level of PhDGK1 increased during conchosporangia maturation in both strains, but increased earlier, and to higher levels, in the early-maturing strain than in the late-maturing strain. This pattern of gene expression was consistent with the patterns of maturity and changes in pigment contents. These results indicate that lipid metabolism plays a key role in regulating conchosporangia maturation in Pyropia spp., and that PhDGK1 might be a useful molecular marker for breeding new early-maturing strains.